Taxonomy Of ‘akhlaq’ In The Governance Of Malaysian Government Procurement Practices - Ramli, Nor Azmi (2022)
Corruption is a global phenomenon. The OECD Report (2016) and NACP report (2019) stated that government procurement is the sector most prone to corruption. Past studies have focused on factors of the Malaysian government procurement system and practice. The focus of this research is on Human Governance philosophy giving emphasis to the physical and spiritual dimension of humans. In-depth research on the aspect of inner ‘Self’ according to al-Ghazali’s framework was done with the research participants to explore the inner factors driving the government procurement practitioners to commit corruption or uphold integrity . The objectives of this research are: (1) To determine the practice of Human Governance in Malaysian government procurement B2G market transactions in influencing decisions to commit corruption or uphold integrity. (2) To identify the criteria for taxonomy of characters which drive the behaviour of the government procurement practitioners to commit corruption or uphold integrity. (3) To examine if the behaviours of corruption and integrity align with the criteria for taxonomy of characters and levels of soul as constructed in the theoretical framework based on al-Ghazali’s thoughts. Research in the form of phenomenology was applied to collect qualitative data based on the experiences of 13 research participants through the interview method. The research result concludes that the participants do not have knowledge of Human Governance philosophy as an internal self-control mechanism in making decisions to avoid being involved with corrupt practice.